1993
DOI: 10.1128/jvi.67.1.131-141.1993
|View full text |Cite
|
Sign up to set email alerts
|

The minor capsid protein VP1 of the autonomous parvovirus minute virus of mice is dispensable for encapsidation of progeny single-stranded DNA but is required for infectivity

Abstract: The two capsid proteins of minute virus of mice, VP1 and VP2, are generated from a single large open reading frame by alternate splicing of the capsid gene mRNA. Examination of the replication of a series of mutants that express only VP1, only VP2, or neither capsid protein demonstrates that VP2 is necessary for the accumulation and encapsidation of virus progeny single-stranded DNA. VP1 is dispensable for these functions but is required to produce an infectious virion. Virus that lacks VP1 binds to cells as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 59 publications
(63 reference statements)
2
32
0
1
Order By: Relevance
“…It has been reported that four basic regions in VP1u exist among animal parvoviruses [CPV, PPV and minute virus of mice (MVM)] [19]. The overall percentage of basic amino acids (arginine and lysine) in the viruses including F27 is summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that four basic regions in VP1u exist among animal parvoviruses [CPV, PPV and minute virus of mice (MVM)] [19]. The overall percentage of basic amino acids (arginine and lysine) in the viruses including F27 is summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Epitopes located in the VP2 capsid protein of PPV are important for generating neutralizing antibodies against this virus, with a high potential to activate B cells. These studies indicate that the N-terminal of VP2 is a strong candidate for B cell epitopes and should be included in vaccines [46,47]. Antibodies that bound to a region composed of amino acids 497-516 were seen soon after the second inoculation and the titers (inferred from the intensity of the phosphatase reactions) were maintained throughout the experiment.…”
Section: Discussionmentioning
confidence: 86%
“…HHP and low temperature HHP simulations displayed small fluctuations during the production run and only the N-terminal region of the VP2 1K3V structure showed changes in configuration (amino acids . Compared with the molecular dynamics of native VP2, the HHP simulation tended to produce fixed turns where interconversion between bends and turns were recorded (amino acids [45][46][47][48][49][50][51][52][53][54][55] whereas low temperature HHP fixed this region in a 3-helix configuration. The region from amino acids 75-85 fluctuated among alpha-helix/turn/3-helix configurations in the native simulation but the region was then fixed as an alpha-helical structure in the HHP run and varied between turns and bends in the low temperature HHP run.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Epitopes located in the VP2 capsid protein of PPV are important for generating neutralizing antibodies against this virus, with a high potential to activate B cells. These studies indicate that the N-terminal of VP2 is a strong candidate for B cell epitopes and should be included in vaccines 40,41 .…”
Section: Discussionmentioning
confidence: 92%